Cost-effectiveness analysis of metronomic capecitabine as adjuvant chemotherapy in locoregionally advanced nasopharyngeal carcinoma - She, Longjiang; Tian, Kun; Han, Jiaqi; Zuo, Weihan; Wang, Zhu; Zhang, Ning (Frontiers in Oncology, 2022)
Background: Adding metronomic capecitabine to concurrent chemoradiotherapy (CCRT) brings failure-free survival (FFS) benefits to patients with locoregionally advanced nasopharyngeal carcinoma (NPC). This study aims to assess the cost-effectiveness of metronomic capecitabine in locoregionally advanced NPC. Methods: We created a Markov model to calculate the expense and health outcomes of metronomic capecitabine in comparison to that observed in locoregionally advanced NPC. Related costs, life-years (LYs), quality adjusted life years (QALYs), and incremental cost-effective ratios (ICERs) were measured at a willingness-to-pay (WTP) threshold of $33585 per QALY. A combination of different sensitivity analyses was used to test for model robustness. Additionally, a subgroup analysis was also performed. Results: In contrast to what is observed in the locoregionally advanced NPC, adding metronomic adjuvant capecitabine yielded an additional 1.11 QALYs with an incremental cost of $10741.59 which obtained an ICER of $9669.99 per QALY. The result of one-way sensitive analysis indicated that the utility of FFS and progression disease (PD), and the cost of follow-up were the most significant factors. The probability of metronomic capecitabine being cost-effective was 97.1% at a WTP of $33585 per QALY. Conclusion: Metronomic capecitabine as adjuvant chemotherapy is a cost-effective strategy for locoregionally advanced NPC patients.